Anti-Drug Education in the Curriculum - Anthony Hanoch Mansawan; Cahyani Mega Ayu Lestari Putri; Christian Nathaniel; Nabila Ramadhani Nugroho (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2021)
Narcotics have been one of the biggest problems in the world of education. In the last 10 years the numbers of narcotics users amongst student have risen significantly. Data from the National Narcotic Agency shows that at least 20 percent of young adult in Indonesia have consumed narcotic. A variety of solution is made to counter this number; one of them is through the learning process at school. A form of drug education is taught at physical education lesson but only as a minor subject. With the rising number of drug abuser among student, a more intensive solution has to be made. The integration of anti-narcotics education in school curriculum is one way to tackle this problem. School curriculum can make sure that all students received education on narcotic and allows for a more intense learning so that student can better understand the danger of narcotics.